All eyes on her - Flynn, Laurie Elizabeth (New York : Imprint, 2020)
". . . You heard the story on the news. A girl and a boy went into the woods. The girl carried a picnic basket. The boy wore bright yellow running shoes. The girl found her way out, but the boy never did... Everyone thinks they know what happened. Some say Tabby pushed him off that cliff--she didn't even like hiking. She was jealous. She had more than her share of demons. Others think he fell accidentally--she loved Mark. She would never hurt him...even if he hurt her. But what's the real story? 'All Eyes On Her' is told from everyone but Tabby herself as the people in her life string together the events that led Tabby to that cliff. Her best friend. Her sister. Her enemy. Her ex-boyfriend. Because everybody thinks they know a girl better than she knows herself. What do you think is the truth? . . ."--Booklist.
School Library Journal, May 2020
Booklist starred, May 2020
Bulletin (Center for Children's Books), July 2020
Young Adult
Keywords: Teenage girls -- Juvenile fiction; Teenage boys -- Death -- Juvenile fiction; Trials (Murder) -- Juvenile fiction; Teenage girls -- Fiction; Teenage boys -- Death -- Fiction; Trials (Murder) -- Fiction